1996
DOI: 10.1159/000237417
|View full text |Cite
|
Sign up to set email alerts
|

Expression of High-Affinity IgE Receptor (FcεRI) on Human Alveolar Macrophages from Atopic and Non-Atopic Patients

Abstract: The expression of high-affinity IgE receptor (FcΕRI) on alveolar macrophages was examined in order to determine the association of alveolar macrophages with IgE-dependent inflammation. Immunostaining showed that a 15–1 monoclonal antibody against FcΕRI α chain reacted with alveolar macrophages from both atopic and non-atopic patients by immunostaining. In addition, preincubation of 15–1 monoclonal antibody specifically blocked monomeric IgE binding to alveolar macrophages. Reverse transcription polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…These data also suggest that all three subunits of FcεRI were simultaneously transcribed. Using reverse transcription (RT‐PCR), the similar mRNA expression for FcεRI subunits has been observed in isolated human alveolar macrophages 24 or eosinophils 10 . Although chimeric receptor consisting of αγ 2 had a similar function to the native FcεRI (αβγ 2 ), 25 it has been demonstrated that the γ‐dimer functions as an autonomous activation module, while β‐functions as a signal amplifier providing a gain of 5‐ to 7‐fold for Syk activation and calcium mobilization 26 …”
Section: Discussionmentioning
confidence: 77%
“…These data also suggest that all three subunits of FcεRI were simultaneously transcribed. Using reverse transcription (RT‐PCR), the similar mRNA expression for FcεRI subunits has been observed in isolated human alveolar macrophages 24 or eosinophils 10 . Although chimeric receptor consisting of αγ 2 had a similar function to the native FcεRI (αβγ 2 ), 25 it has been demonstrated that the γ‐dimer functions as an autonomous activation module, while β‐functions as a signal amplifier providing a gain of 5‐ to 7‐fold for Syk activation and calcium mobilization 26 …”
Section: Discussionmentioning
confidence: 77%
“…These events can lead to a domino effect where more IgE produced by B cells may become involved in forming more immune complexes resulting in further exacerbation of airway inflammation. Second, Fc⑀RI is expressed by some types of APC, including monocytes (35), dendritic cells (36), and alveolar macrophages (37), and the IgE immune complexes may be more readily captured by these cells and processed for Ag presentation. Our results with Fc⑀RI-deficient mice indeed support a critical role for Fc⑀RI in the augmented responses induced by IgE immune complexes.…”
Section: Discussionmentioning
confidence: 99%
“…FcεRI(αγ) are expressed by human alveolar macrophage in asthmatic patients (22). We therefore examined FcγRIV on mouse alveolar macrophages.…”
Section: Human Fcεri(αγ) Is a Functional Equivalent Of Mouse Fcγrivmentioning
confidence: 99%
“…Although hFcεRI has a high affinity whereas mFcγRIV has a low affinity for IgE, both can be engaged by IgE ICs. Moreover, hFcεRI is expressed without FcRβ in macrophages and neutrophils and especially in atopic patients (13,22). Mouse macrophage/neutrophil FcγRIV and human macrophage/neutrophil FcεRI(αγ) therefore have the same quaternary structure: an IgE-binding subunit and the same ITAMcontaining FcRγ subunit.…”
Section: Human Fcεri(αγ) Is a Functional Equivalent Of Mouse Fcγrivmentioning
confidence: 99%